2017
DOI: 10.3892/or.2017.5597
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of MMP-2 and −9 secretion by cytokines, inducers and inhibitors in human melanoma A-2058 cells

Abstract: Abstract. Melanoma, an extremely aggressive cancer, causes the most skin cancer-related deaths, due to metastasis to other areas of the body, such as lymph nodes, lungs, liver, brain or bone. It is characterized by high levels of matrix metalloproteinase (MMP)-2 and -9 secretions that degrade the extracellular matrix and basement membrane, allowing cancer cells to spread to distal organs. Various cytokines, mitogens, growth factors, inducers and inhibitors control MMP activities. We investigated the roles of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Li et al found that reducing the expression of MMP-9 in prostate cancer cells was accompanied by a decrease in cell invasion and migration [16]. Since we found that SPUP-treated cells inhibit the migration of prostate cancer, we hypothesized that SPUP exerts the effect through cancer cell invasion and metastasis-promoting factor MMP-9 [17] and then found that the higher the concentration of SPUP, the lower the expression of MMP-9, indicating that SPUP may suppress cell migration by inhibiting the expression of MMP-9 protein. In terms of induction of apoptosis, DU145 cells were treated with different SPUP concentrations (25, 50, 100, and 200 μg/ml) for 72 h, and the results indicated that SPUP can induce apoptosis in a dose-dependent manner in DU145 cells.…”
Section: Discussionmentioning
confidence: 85%
“…Li et al found that reducing the expression of MMP-9 in prostate cancer cells was accompanied by a decrease in cell invasion and migration [16]. Since we found that SPUP-treated cells inhibit the migration of prostate cancer, we hypothesized that SPUP exerts the effect through cancer cell invasion and metastasis-promoting factor MMP-9 [17] and then found that the higher the concentration of SPUP, the lower the expression of MMP-9, indicating that SPUP may suppress cell migration by inhibiting the expression of MMP-9 protein. In terms of induction of apoptosis, DU145 cells were treated with different SPUP concentrations (25, 50, 100, and 200 μg/ml) for 72 h, and the results indicated that SPUP can induce apoptosis in a dose-dependent manner in DU145 cells.…”
Section: Discussionmentioning
confidence: 85%
“…Recent data have shown that upon melanoma cell lines, TNF and IL-1 showed no significant overall effect on expression of molecules involved in metastatic processes. Nevertheless, arrays of cytokines/chemokines and various regulatory molecules (e.g., matrix metalloproteinases) can modulate this process [ 34 ]. Our previous human reported TNF values [ 15 ] were as well low and, as prior signaled by us, the low registered circulatory levels can account for the multiplexing assays that use specific antibodies for different circulatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of the ECM is an important step in tumor cell invasion. Although various proteases are involved in ECM degradation, MMPs, a family of zinc and calcium-dependent proteolytic enzymes, digest many components of ECM [32]. MMPs are important to cell migration/invasion and metastasis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although various proteases are involved in ECM degradation, MMPs, a family of zinc and calcium-dependent proteolytic enzymes, digest many components of ECM [32]. MMPs are important to cell migration/invasion and metastasis [32]. At least more than 20 different MMPs work on multiple substrates including collagen types I, II, III, IV and stromyelin [32,33].…”
Section: Discussionmentioning
confidence: 99%